Recent Advancements of Monotherapy, Combination, and Sequential Treatment of EGFR/ALK-TKIs and ICIs in Non-Small Cell Lung Cancer - Dehua Liao; Lun Yu; Dangang Shangguan; Yongchang Zhang; Bowen Xiao; Ni Liu; Nong Yang (Frontiers Media S.A., 2022)
Lung cancer is the leading cause of cancer-related deaths with high morbidity and mortality. Non-small cell lung cancer (NSCLC) is the most common type of lung cancer, accounting for 85% of all cases. Fortunately, the development of molecular oncology provides a promising and effective therapeutic strategy for lung cancers, including specific gene mutations/translocations and immune checkpoints, with epidermal growth factor receptor (EGFR) common mutations first and anaplastic lymphoma kinase (ALK) translocations later as the targeted therapy and immune checkpoint inhibitors (ICIs) as immunotherapy. This review summarized the recent therapy advancements of TKIs and ICIs in NSCLC and focused on the clinical effect of combination or sequential treatment so as to provide the effective advice for the treatment of NSCLC.